PENERAPAN PROJECT-BASED LEARNING BERBASIS KARYA TULIS ILMIAH UNTUK MENINGKATKAN KOMPETENSI ABAD 21 DI SEKOLAH DASAR - Nurrahman, Nurrahman; Aziz, Abd; Afif, Nur (Institut PTIQ Jakarta, 2025)
The purpose of this study was to determine how effective the project-based learning (PjBL) model, which relies on scientific paper assignments, is in instilling modern skills in elementary schools. Data were collected at SD Insan Cendekia Madani BSD through observation, interviews, and document analysis. A descriptive qualitative approach and case study design were used to collect data. This study shows that the implementation of PjBL is carried out in stages, starting from planning, implementation, to evaluation. Teachers play an active role in helping students compile and present scientific papers. This model encourages students to think critically, work together in teams, write better, and speak well through presentations. However, the implementation process still faces several challenges. These include time constraints, lack of teacher training in scientific approaches, and suboptimal curriculum and infrastructure support. Overall, this method has considerable potential to provide students with an applicable, contextual learning experience that is in accordance with the demands of the 21st century, especially in the context of elementary education